Mediating effect of successful aging on the relationship between psychological resilience and death anxiety among middle-aged and older adults with hypertension - Wang, Meiding; Zhang, Lin; Ma, Jianing; Sun, Hong; Gao, Ziyun; Hu, Mengya; Liu, Haiyang; Guo, Leilei (Frontiers in Public Health, 2023)
Objective: The aging trend of China's population is severe and successful aging (SA) is imminent. Aging can lead to various chronic diseases, with hypertension being the most common. Due to this lifelong disease, patients suffer from many anxieties, as death anxiety (DA) can be the most prevalent. It has been suggested that psychological resilience (PR) can reduce DA. Therefore, this study aimed to analyze the mediating effect of SA between PR and DA in middle-aged and elderly patients with hypertension. Methods: A cross-sectional survey was designed. From August to December 2021, 298 middle-aged and elderly hypertensive patients were selected by multistage cluster random sampling in three districts of Jinzhou City, Liaoning Province. They were surveyed using the demographic questionnaires, the Conner-Davidson Resilience Scale, the Successful Aging Inventory, and the Chinese version of a Likert-type Templer-Death Anxiety Scale. Descriptive analyses, independent sample T-test, and one-way analysis of variance (ANOVA) were used to describe demographic characteristics among hypertensive patients with different characteristics, respectively. Statistics were considered significant when P < 0.05. Pearson correlation coefficients describe the relationship between PR, SA, and DA. The research model was shaped through Structural Equation Modeling (SEM). SPSS PROCESS macro was used to verify the mediation model. A binary logistic regression model was used with DA as the dependent variable. Results: The scores for PR, SA, and DA in hypertensive patients are (49.52 ± 14.38) points, (51.22 ± 7.63) points, and (46.67 ± 9.03) points. PR was negatively correlated with DA (r =-0.307, P <0.01). Moreover, incorporating SA as a mediating variable in PR and DA, SA was positively correlated with PR (r =0.335, P <0.01) and DA (r =0.085, P >0.05). The opposite sign of the direct and indirect effects indicates that SA shows a suppression effect between PR and DA, with a percentage of 20.7%. Good self-assessed health status (0.058 [0.018, 0.184]) may be a protective factor for DA. Conclusion: Medical professionals should improve the PR of middle-aged and elderly patients with hypertension through interventions that reduce DA and increase the likelihood of SA.